Genome-wide association studies using multi-models and multi-SNP datasets provide new insights into pasmo resistance in flax - He, Liqiang; Sui, Yao; Che, Yanru; Wang, Huixian; Rashid, Khalid Y.; Cloutier, Sylvie; You, Frank M. (Frontiers in Plant Science, 2023)
Flax (Linum usitatissimum L.) is an economically important crop due to its oil and fiber. However, it is prone to various diseases, including pasmo caused by the fungus Septoria linicola. In this study, we evaluated 445 flax accessions over five years (PAS2012-PAS2016) and conducted genetic analyses to identify factors loci associated with pasmo resistance. We used 246,035 SNPs to analyze the genetic structure of the population and identified five subpopulations. Using several statistical models, including the single-locus model GEMMA and the multi-locus models FarmCPU, mrMLM, and 3VmrMLM, we identified 372 significantputative quantitative trait nucleotides (QTNs) or 1320 tag QTNs associated with pasmo resistance from six pasmo resistance datasets (PAS2012-PAS2016 and the average of them, namely PASmean) and three genotypic datasets (the all SNPs/ALL, the genebased SNPs/GB and the RGA-based SNPs/RGAB). The tag QTNs had R 2 values of 0.6610-16.98% from the ALL SNPs dataset, 0.6801-20.54% from the GB SNPs dataset, and 0.5201-22.42% from the RGAB SNPs dataset. Of these tag QTNs, 93 were novel. Additionally, 373 resistance gene analogs (RGAs) co-localizing with 395 tag QTNs were considered as potential candidates for controlling pasmo resistance in flax and 50 QTN-by-environment interactions (QEIs) were identified to account for genes and environmental interactions. Nine RGAs were predicted as candidate genes for ten QEIs.Our results suggest that pasmo resistance in flax is polygenic and potentially influenced by environmental factors. The identified QTNs provide potential targets for improving pasmo resistance in flax breeding programs. This study sheds light on the genetic basis of pasmo resistance and highlights the importance of considering both genetic and environmental factors in breeding programs for flax.